Metabolic Regulation of “Ca. Methylacidiphilum Fumariolicum” SolV Cells Grown Under Different Nitrogen and Oxygen Limitations - Khadem, Ahmad F.; Pol, Arjan; Wieczorek, Adam S.; Jetten, Mike S.M.; Op Den Camp, Huub J. (Frontiers in Microbiology, 2012)
Aerobic methanotrophic bacteria can use methane as their sole energy source. The discovery of “Ca. Methylacidiphilum fumariolicum” strain SolV and other verrucomicrobial methanotrophs has revealed that the ability of bacteria to oxidize CH4 is much more diverse than has previously been assumed in terms of ecology, phylogeny, and physiology. A remarkable characteristic of the methane-oxidizing Verrucomicrobia is their extremely acidophilic phenotype, growing even below pH 1. In this study we used RNA-Seq to analyze the metabolic regulation of “Ca. M. fumariolicum” SolV cells growing at μmax in batch culture or under nitrogen fixing or oxygen limited conditions in chemostats, all at pH 2. The analysis showed that two of the three pmoCAB operons each encoding particulate methane monoxygenases were differentially expressed, probably regulated by the available oxygen. The hydrogen produced during N2 fixation is apparently recycled as demonstrated by the upregulation of the genes encoding a Ni/Fe-dependent hydrogenase. These hydrogenase genes were also upregulated under low oxygen conditions. Handling of nitrosative stress was shown by the expression of the nitric oxide reductase encoding genes norB and norC under all conditions tested, the upregulation of nitrite reductase nirK under oxygen limitation and of hydroxylamine oxidoreductase hao in the presence of ammonium. Unraveling the gene regulation of carbon and nitrogen metabolism helps to understand the underlying physiological adaptations of strain SolV in view of the harsh conditions of its natural ecosystem.